2018
DOI: 10.1021/acs.energyfuels.7b03955
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dissolved Oxygen on Water Imbibition in Gas Shales

Abstract: Understanding the water uptake of gas shales is critical for designing and optimizing hydraulic fracturing operations during which a large volume of fracturing water containing dissolved oxygen is injected into tight reservoirs. Recent studies show that the dissolved oxygen may promote oxidation reactions which can affect salinity and pH value of flowback water; however, the effects of dissolved oxygen and oxidation reactions on water imbibition into the shale matrix and on the concentration of individual ions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 65 publications
2
22
0
Order By: Relevance
“…Because O 2 is present in FRW and atmospheric O 2 is entrained in the injected FRW (Xu et al, 2018; Zolfaghari et al, 2016) and other oxidizers (such as a persulfate breaker or H 2 O 2 ) are added to fracturing fluids at shale gas sites (Osselin et al, 2019; Phan et al, 2020), and because there are always pyrite minerals in shales (Heller & Zoback, 2014), oxidation of pyrites after hydraulic fracturing and during initial flowback is very likely (Osselin et al, 2019; Paukert Vankeuren et al, 2017; Xu et al, 2018; Zolfaghari et al, 2016). Laboratory experiments have revealed evidence for oxidation of pyrites (Pearce et al, 2018; Xu et al, 2018; d and e in Figure 4), which would contribute additional SO 4 to the FBW. However, in our field experiment, even an additional 10 mg/L of SO 4 derived from the oxidation of pyrite in the shale at the initial stage of flowback (158 + 10 mg/L) would deviate from the mixing line (g in Figure 4), suggesting that the data did not provide evidence for pyrite oxidation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Because O 2 is present in FRW and atmospheric O 2 is entrained in the injected FRW (Xu et al, 2018; Zolfaghari et al, 2016) and other oxidizers (such as a persulfate breaker or H 2 O 2 ) are added to fracturing fluids at shale gas sites (Osselin et al, 2019; Phan et al, 2020), and because there are always pyrite minerals in shales (Heller & Zoback, 2014), oxidation of pyrites after hydraulic fracturing and during initial flowback is very likely (Osselin et al, 2019; Paukert Vankeuren et al, 2017; Xu et al, 2018; Zolfaghari et al, 2016). Laboratory experiments have revealed evidence for oxidation of pyrites (Pearce et al, 2018; Xu et al, 2018; d and e in Figure 4), which would contribute additional SO 4 to the FBW. However, in our field experiment, even an additional 10 mg/L of SO 4 derived from the oxidation of pyrite in the shale at the initial stage of flowback (158 + 10 mg/L) would deviate from the mixing line (g in Figure 4), suggesting that the data did not provide evidence for pyrite oxidation.…”
Section: Resultsmentioning
confidence: 99%
“…However, FBW samples do not plot perfectly on a Rayleigh fractionation trend for sulfate reduction (process a, b, and c in Figure 4) with S isotope enrichment factors ranging from −60‰ to −9‰ (Krouse & Mayer, 2000; Mayer et al, 2007). Because O 2 is present in FRW and atmospheric O 2 is entrained in the injected FRW (Xu et al, 2018; Zolfaghari et al, 2016) and other oxidizers (such as a persulfate breaker or H 2 O 2 ) are added to fracturing fluids at shale gas sites (Osselin et al, 2019; Phan et al, 2020), and because there are always pyrite minerals in shales (Heller & Zoback, 2014), oxidation of pyrites after hydraulic fracturing and during initial flowback is very likely (Osselin et al, 2019; Paukert Vankeuren et al, 2017; Xu et al, 2018; Zolfaghari et al, 2016). Laboratory experiments have revealed evidence for oxidation of pyrites (Pearce et al, 2018; Xu et al, 2018; d and e in Figure 4), which would contribute additional SO 4 to the FBW.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, studies showed that the dissolved oxygen in the fracturing fluid could create an oxic condition in the shale reservoirs [19,33]. Pyrite (FeS 2 ) is a reductive sulfide with iron (II) which is stable only at very low oxidation states, and the pyrite in shale can be easily oxidized under the atmospheric oxygen and water environment [24,34].…”
Section: Geofluidsmentioning
confidence: 99%
“…Although experiments of water-rock interactions at the laboratory scale offered valuable preliminary data on physical-chemical interactions between shale and fracturing fluid, most of these imbibition experiments were performed at low temperature and low pressure [15][16][17]. Considering that the reservoir usually has high-temperature and high-pressure conditions [18], the experiments performed at reservoir temperature and pressure are more approximate conditions in the field [19].…”
Section: Introductionmentioning
confidence: 99%